Efficient drug delivery for cancer treatment using amine-functional SiO2-LDH nanocomposites - Li, L.; Gu, Z.; Gu, W.; Liu, Jian; Xu, Z. (2015)
Copyright 2015 by TechConnect. All rights reserved.Well-dispersed Si02 nanodot-coated LDH nanohybrids have been prepared via a nanodot-coating strategy. Si02@LDH nanohybrids show good dispersion in aqueous solution and cell culture medium. The anticancer delivery test demonstrates significant inhibition of cancer cell proliferation using Si02@LDH nanohybrids to deliver methotrexate (MTX).